2014
DOI: 10.1111/bph.12506
|View full text |Cite
|
Sign up to set email alerts
|

The cognition‐enhancing activity of E1R, a novel positive allosteric modulator of sigma‐1 receptors

Abstract: BACKGROUND AND PURPOSEHere, we describe the in vitro and in vivo effects of (4R,5S)-2-(5-methyl-2-oxo-4-phenyl-pyrrolidin-1-yl)-acetamide (E1R), a novel positive allosteric modulator of sigma-1 receptors. EXPERIMENTAL APPROACHE1R was tested for sigma receptor binding activity in a ]i) assays and in an electrically stimulated rat vas deferens model. E1R's effects on cognitive function were tested using passive avoidance (PA) and Y-maze tests in mice. A selective sigma-1 receptor antagonist (NE-100), was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Previously we showed that E1R, a phenylpiracetam derivative, is selective positive allosteric Sig1R modulator [18,38]. In this study E1R showed anti-convulsive effects both in PTZ-and BIC-induced seizure models.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Previously we showed that E1R, a phenylpiracetam derivative, is selective positive allosteric Sig1R modulator [18,38]. In this study E1R showed anti-convulsive effects both in PTZ-and BIC-induced seizure models.…”
Section: Discussionsupporting
confidence: 54%
“…This allows us to confirm the anti-convulsive properties of positive allosteric Sig1R modulators and the role of Sig1R in the mode of action of these compounds. Among all positive allosteric Sig1R modulators, E1R is the only one known modulator that possesses memory-improving effects [18]. Phenytoin treatment on epilepsy has been shown to induce learning and memory deficit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E1R augmented the binding of [ 3 H]ditolylguanidine, a nonselective sigma receptor radioligand, but was not able to show any allosteric effect on sigma-1 receptors using [ 3 H](+)-pentazocine, a sigma-1 receptor agonist 70 (Figure 8). E1R did not increase contractions in the vas deferens assay when co-administered with PB-28, a sigma-2 receptor agonist, but did potentiate the effect of PRE-084 upon bradykinin-induced intracellular Ca 2+ increase in vitro.…”
Section: Sigma-1 Receptormentioning
confidence: 99%